Public knowledge, attitudes, and practices toward heat stroke in Ningbo, China: a cross-sectional study - Zhang, Wei; Feng, Yangrong; Chai, Shuren; Yang, Zheng; Dong, Jing (Frontiers in Public Health, 2025)
BackgroundHeat stroke, a severe heat illness with high mortality rates, is increasingly prevalent due to rising temperatures. This study aimed to assess public knowledge, attitudes, and practices (KAP) regarding heat stroke.MethodsWe conducted a cross-sectional study in Ningbo City from December 10, 2023, to March 21, 2024. Data were collected using a structured, self-administered electronic KAP questionnaire designed to assess knowledge, attitudes, and practices regarding heat stroke. Statistical analysis was performed using SPSS 27.0 and AMOS 26.0, including descriptive statistics, correlation analysis, logistic regression, and structural equation modeling (SEM).ResultsThe study enrolled 467 participants, of whom 396 (84.81%) were aged between 18 and 45 years, and 294 (62.96%) were female. The median scores for knowledge, attitude, and practice exceeded 80% of their respective total score dimensions, at 26(range: 23–26), 35(range: 33–35), and 40 points (range: 35–44). Structural equation modeling (SEM) showed direct impacts of knowledge on attitude (β = 0.276, p = 0.009) and direct influences of both knowledge (β = 0.133, p = 0.012) and attitude (β = 0.431, p = 0.012) on practice. Moreover, knowledge indirectly affected practice through its impact on attitude (β = 0.119, p = 0.008). Multivariate logistic regression found that attitude score (OR = 1.555, p < 0.001), BMI under 18(OR = 4.135, p = 0.024), marital status (married: OR = 0.433, p = 0.001), and Bachelor’s degree and below (High school/vocational school and below: OR = 0.294, p = 0.013; junior college: OR = 0.340, p = 0.018; bachelor’s degree: OR = 0.410, p = 0.027) correlated with practice scores.ConclusionWhile the Ningbo public showed sufficient general understanding of heat stroke, the study found serious gaps in understanding specific risk factors and preventive measures. The findings suggest tailored health education programs, particularly for young people and less educated populations, to promote community-wide awareness and prevention.